Antioxidant, Antimicrobial and Cytotoxic Activities of Desmodium Motorium Merr. - Alam, M. A.; Pal, T. K.; Chowdhury, M. A.; Rashid, M. A.; Rahaman, M. S. (Journal of Scientific Research, 2012)
The n-hexane, carbon tetrachloride, dichloromethane soluble fractions of methanol extract of the whole plant of Desmodium motorium were subjected to antioxidant activity by indicated method, inhibition of microbial growth by disc diffusion method and cytotoxicity by brine shrimp lethality bioassay. The methanol i.e., crude extract showed highest antioxidant activity having IC50 9.5 ?g/ml as compared to 9.0 ?g/ml for standard agent BHT. The n-hexane, carbon tetrachloride and dichloromethane soluble fraction showed moderate inhibitory activity to microbial growth, while all the extractive exhibited strong cytotoxic property with the carbon tetrachloride soluble materials revealed the strongest cytotoxicity with LC50 1.54 ?g/ml. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.10955 J. Sci. Res. 5 (1), 201-205 (2013)